Computational intelligence in software modeling - Jain, Vishal 1983-; Chatterjee, Jyotir Moy; Bansal, Ankita; Köse, Utku 1985-; Jain, Abha (De Gruyter, 2022)
THE SERIES: FRONTIERS IN COMPUTATIONAL INTELLIGENCE The series Frontiers In Computational Intelligence is envisioned to provide comprehensive coverage and understanding of cutting edge research in computational intelligence. It intends to augment the scholarly discourse on all topics relating to the advances in artifi cial life and machine learning in the form of metaheuristics, approximate reasoning, and robotics. Latest research findings are coupled with applications to varied domains of engineering and computer sciences. This field is steadily growing especially with the advent of novel machine learning algorithms being applied to different domains of engineering and technology. The series brings together leading researchers that intend to continue to advance the field and create a broad knowledge about the most recent research. Series Editor Dr. Siddhartha Bhattacharyya, CHRIST (Deemed to be University), Bangalore, India Editorial Advisory Board Dr. Elizabeth Behrman, Wichita State University, Kansas, USA Dr. Goran Klepac Dr. Leo Mrsic, Algebra University College, Croatia Dr. Aboul Ella Hassanien, Cairo University, Egypt Dr. Jan Platos, VSB-Technical University of Ostrava, Czech Republic Dr. Xiao-Zhi Gao, University of Eastern Finland, Finland Dr. Wellington Pinheiro dos Santos, Federal University of Pernambuco, Brazil
Keywords: bicssc / Algorithms & data structures; bicssc / Software Engineering; bicssc / Computer networking & communications; bicssc / Artificial intelligence; bisacsh / COM016000 COMPUTERS / Computer Vision & Pattern Recognition; bisacsh / COM032000 COMPUTERS / Information Technology; bisacsh / COM044000 COMPUTERS / Neural Networks; bisacsh / COM051000 COMPUTERS / Programming / General; bisacsh / COM051230 COMPUTERS / Software Development & Engineering / General; bisacsh / COM051300 COMPUTERS / Programming / Algorithms; bisacsh / TEC037000 Technology & Engineering / Robotics; Künstliche Intelligenz; Softwareentwicklung; Hardcover, Softcover / Informatik, EDV/Informatik